Investigation of exposure to occupational noise among forestry machine operators: A case study in Brazil - Camargo, Diego Aparecido [UNESP]; Munis, Rafaele Almeida [UNESP]; Simões, Danilo [UNESP] (MDPI, 2021)
In mechanized harvesting of wood operations, in a cut-to-length system, occupational noise is emitted by self-propelled forest machines, which compromises the safety and health of operators. Therefore, the occupational noise levels emitted by self-propelled forestry machines, in a cut-to-length system, were investigated to determine which are in line with current Brazilian legislation. The noise levels issued by 22 self-propelled forestry machines in the mechanized harvesting of wood operations, in Eucalyptus and Pinus planted forests, were collected during a full day of measurement. Taking into account the operations performed and the type of planted forest, homogeneous groups of operators were formed. Based on Regulatory Norms N.9 and N.15 adopted for labor purposes in Brazil, occupational noise levels were analyzed. In relation to harvester operators, 36.4% were exposed to values above the exposure limit of 85 dB (A) and 63.6% to the action level of 80 dB (A). Regarding the forwarder operators, 100% were exposed to values that exceeded the action level. For the analyzed conditions, for the cut-to-length system employed in harvesting wood in forest planted with Eucalyptus and Pinus, the occupational noise levels of the self-propelled forest machines are not in line with current Brazilian legislation for labor purposes.
Keywords: Cut-to-length logging; Ergonomic risk; Eucalyptus; Forest management; Hearing protection; Pinus; Worker’s health